2008
DOI: 10.1097/nmd.0b013e31815fa4e7
|View full text |Cite
|
Sign up to set email alerts
|

Dissociative Disorders and Suicidality in Psychiatric Outpatients

Abstract: Although it is common for patients with dissociative disorders to report a history of suicide attempts, there is very little data systematically comparing suicidality in patients with dissociative disorders versus patients without these disorders. The subjects in our study were 231 patients consecutively admitted to an inner-city, hospital-based outpatient psychiatric clinic. Eighty-two of these patients completed structured interviews for dissociative disorders, borderline personality disorder, and trauma his… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

15
100
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 177 publications
(116 citation statements)
references
References 39 publications
15
100
1
Order By: Relevance
“…Some clinicians experienced in the treatment of DDs have noted that many of their patients, particularly with DID and DDNOS-I, have both considerable comorbidity and low levels of functioning (Kluft, 1999;Van der Hart et al, 2006). This is in line with previous studies that found a high comorbidity and an extensive psychiatric treatment history in DID subjects (Putnam et al, 1986;Ross et al, 1989;Boon & Draijer, 1993;Ellason et al, 1996;Dell, 1998), as well as a strong association with self-harming behavior and suicidality (Foote et al, 2008). However, there is a need for systematic research on the functional impact of DDs.…”
Section: Introductionsupporting
confidence: 90%
“…Some clinicians experienced in the treatment of DDs have noted that many of their patients, particularly with DID and DDNOS-I, have both considerable comorbidity and low levels of functioning (Kluft, 1999;Van der Hart et al, 2006). This is in line with previous studies that found a high comorbidity and an extensive psychiatric treatment history in DID subjects (Putnam et al, 1986;Ross et al, 1989;Boon & Draijer, 1993;Ellason et al, 1996;Dell, 1998), as well as a strong association with self-harming behavior and suicidality (Foote et al, 2008). However, there is a need for systematic research on the functional impact of DDs.…”
Section: Introductionsupporting
confidence: 90%
“…Furthermore, we expected that patients in the earlier stages of treatment, who struggle with safety issues such as self-injurious behaviour and suicidality (e.g. Coons & Milstein, 1990; Foote, Smolin, Neft, & Lipschitz, 2008), would incur greater treatment costs compared to patients in the later stages of treatment.…”
Section: Highlightsmentioning
confidence: 99%
“…Presence of a dissociative disorder is strongly associated with all measures of self-harm and suicidality (45). Self-destructive behavior is very common in the cases of DID.…”
Section: Discussionmentioning
confidence: 99%